Edukasi Penyakit Mulut dan Kuku serta Pengolahan Daging pada Masyarakat Desa Pangkal Jaya (Kabupaten Bogor) untuk Mencegah Penularan Penyakit pada Hewan Berkuku Belah - Budiono, Novericko Ginger; Afni, Niama Vinka Nur; Anidya, Dea Khalissa; Najibah, Syaikhah; Manisyah, Manisyah; Sudrajat, Agum Hideo; Gusthama, Raihandika; Akbar, Roro Intan Sasmaya; Mahdiansyah, Fauzan Luqmannnurhakim; Sarita, Nur Rahmah; Ummah, Fadhilah (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2023)
Foot and mouth disease (FMD) is caused by a viral infection (Genus Aphthovirus; Family Picornaviridae) that infects split-toed animals. This disease impacts the economic, social, and cultural sectors. Indonesia has been free of FMD since 1986, verified by the World Organization of Animal Health in 1990. FMD reappeared as a re-emerging animal disease in Indonesia on June 25, 2022, based on the Decree of the Minister of Agriculture of the Republic of Indonesia No. 500.1/KPTS/PK/300/M/06/2022. Although Pangkal Jaya Village, Nanggung District, Bogor District has yet to become an outbreak area, according to the Ministry of Agriculture, education for residents is also needed regarding this disease to prevent more comprehensive transmission. Education is also emphasized that FMD is not transmitted from animal to human. Education on FMD and procedures for processing meat from animals infected with FMD is carried out by presenting material with power points, pamphlets, and posters. Participants were very enthusiastic about participating in the socialization activities, with the number of participants exceeding expectations and a positive response from the participants to the activities. This activity increased public knowledge by being represented by 3 participants who correctly answered each of the questions given during the interactive quiz session at the end of the activity. After the socialization, residents can learn about the procedures for properly handling meat from animals that suffer from FMD so that it is safe for human consumption, as well as an effort to prevent transmission to other sensitive animals.